STUDI GAYA DESAIN POSMODERN PADA INTERIOR FOOD COURT GALAXY MALL DI SURABAYA - Emmerich, Reiner Franzie; Sari, Sriti Mayang (Dimensi Interior, 2012)
A food court is an important public facilty in a shopping centre. Apart from its generally large capacity and variety of cuisine served, the design of most foodcourts are also generally attractive.Their interior designs are able to affect the atmoshphere and mood of visitors.Many foodcourts in today’s malls adopt the postmodern style in their design, for instance, the Galaxy Mall in Surabaya, which will be the object for case study in this research. The objective of this research is to investigate the implementation of the Post modern style in the interior elements of the food court that will be discussed in detail. The research findings show that the use of Post modern style can be seen in the spatial arrangement, interior elements such as floors, walls and ceilings, furnitures as well as decorative elements such as colour and material. All these elements adopted the Post Modern style in terms of ideology, concept, aim as well as design methodology. The concept of Contradiction has been applied in the two areas of the food court.